Availability and reliability assessment of production systems using simulations. Issue 1 (May 2020) - Napitupulu, Humala; Nurhayati,
Abstract: Reliability assessments in the industry is needed to support production planning, facility maintenance, and other related matters. The reliability of an equipment is usually assessed based on the operating period of its components. Likewise the reliability of the system can be assessed based on the reliability of the subsystem. Assessment of the reliability of production systems as a combination of a number of subsystems can be done using analytical models suitable for series and parallel arrangements. For complex production systems, valuation can use a combination of series and parallel models. But for a production system that consists of a lot of equipment in a series arrangement, evaluations using analytical models will provide low reliability that does not reflect real conditions. In the industry studied, the reliability of the system with 14 subsystems in a series arrangement is around 0.2%. Therefore, reliability assessment needs to be done by simulation. Using the proposed simulation model, the reliability of the system obtained is around 90.4%. This assessment shows that the assessment of the reliability of the production system is more appropriate using simulations, and the proposed simulation model can be used in reliability assessments